2007
DOI: 10.2164/jandrol.106.001271
|View full text |Cite
|
Sign up to set email alerts
|

Tag STS in the AZF Region Associated With Azoospermia in a Tunisian Population

Abstract: The aim of this study was to determine the appropriate tag sequence tagged site (STS) associated with azoospermia. We evaluated the incidence of Y chromosome microdeletions in Tunisian infertile male patients by polymerase chain reaction using 14 STSs in the azoospermia factor (AZF) region of Yq11. A logistic regression analysis was performed to test the association of STSs with semen quality. Haploview version 3.11 was used to identify the possible blocks of deletion involving a minimum number of STSs and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The prevalence in azoospermic men in the present study was similar to that reported by Foresta et al [16]. The prevalence in oligospermic men was higher than what most studies have reported [17], but it was similar to that reported in a Tunisian population [18].…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence in azoospermic men in the present study was similar to that reported by Foresta et al [16]. The prevalence in oligospermic men was higher than what most studies have reported [17], but it was similar to that reported in a Tunisian population [18].…”
Section: Discussionsupporting
confidence: 89%
“…The reported frequencies of deletions in the AZF region vary from 1 to 55%, depending on the inclusion criteria and possibly on the STS markers used for screening, however, mostly an incidence below 15% is reported (22,23). In this study, 11 STS markers, including 6 STS strongly recommended by the European Molecular Genetics Quality Network (EMQN) and the European Academy of Andrology (EAA) guidelines, were used (14).…”
Section: Discussionmentioning
confidence: 93%
“…In our study, the absence of association between obesity and male infertility was due to the genetic background of infertile patients. In fact, in other study, we found that the male infertility was associated with AZF polymorphism (Hadjkacem Loukil et al ., ).…”
Section: Discussionmentioning
confidence: 97%